Implementasi Nilai Pendidikan Islami melalui Filosofi Gusjigang bagi Masyarakat Kudus Kulon - Septy Nadia Salma (Mitra PGMI: Jurnal Kependidikan MI, 2022)
The purpose of this research is to find out how to implement Islamic educational values in Gusjigang philosophy in Kudus Kulon. Gusjigang's philosophy has noble values that have been taught and applied by the people of Kudus Kulon. So the cultivation of Gusjigang Islamic educational values can be continued by today's young generation to be used as guidelines for daily activities. This type of research is a phenomenological research with a qualitative approach. Data collection techniques through interviews. Then analyzed into meaningful information for the reader. The setting of this research was carried out in the Kudus Tower community area. The subjects of this research are the people of Kudus Kulon, the manager of the Gusjigang Kudus store, and the shops around the Kudus tower. The results of this study indicate the values of Islamic education contained in Gusjigang, namely there are 6 values philosophical, moral, scientific, spiritual, artistic, and economic. The implications of Gusjigang have a positive impact on society. The implications are Good: good manners, good morals in carrying out daily activities, Ngaji: knowledgeable, and able to practice it to others, Trade: diligent in trading, trade and worship run in a balanced way